STRUCTURAL ANALYSIS - Hibbeler Russell C (Prentice Hall, 1995)
TYPES OF STRUCTURES AND LOANS ANALYSIS OF STATICALLY DETERMINATE STRUCTURES ANALYSIS OF STATICALLY DETERMINATE TRUSSES INTERNAL LOADINGS DEVELOPED IN STRUCTURAL MEMBERS
TYPES OF STRUCTURES AND LOANS ANALYSIS OF STATICALLY DETERMINATE STRUCTURES ANALYSIS OF STATICALLY DETERMINATE TRUSSES INTERNAL LOADINGS DEVELOPED IN STRUCTURAL MEMBERS